Peningkatkan Kemampuan Promosi Online Taman Lazuardi Desa Susukan, Sumbang, Kabupaten Banyumas Melalui Pembuatan Video - Nuryanti Nuryanti; Mite Setiansah; Dwi Pangastuti Marhaeni; Sri Pangestuti; Adinna Islah Perwita (Universitas Muhammadiyah Surakarta, 2023)
Taman Lazuardi as one of the tourist destinations of Susukan Village, of course it requires promotion in order to attract tourists to come to Taman Lazuardi. Taman lazuardi promotion team has used several social media platforms as promotional tools, but the results are still not optimal. One of the reasons is the lack of skills to create interesting content. One of the content that according to the promotion team is not yet attractive is content in the form of promotional videos. Therefore, it is necessary to provide training in create videos for promotional purposes through social media which can ultimately attract tourists. The service implementation team in this case will cooperate with the Taman Lazuardi promotion team in Susukan Village, Susukan, Banyumas. The method used to overcome partner problems is to do some training sessions and accompaniment. The result of this activity was the creation of 7 promotional videos made by Susukan residents and uploaded to Taman Lazuardi's social media.